Increasing Public Awareness on the Prevention of Dengue Hemorrhagic Fever through the Utilization of Used Cooking Oil into Lavender Aromatherapy Candles in Krompaan Village - Aisyah Shafa Nadia S; Dea Maulida Afifah; Aniq Rizkyana; Raifa Futri Haryono (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
Dengue Hemorrhagic Fever or known as DBD disease which is caused by a dengue virus caused by the Aedes Aegypti mosquito. The disease causes sufferers to experience severe pain, complications, and death. The UIN Walisongo KKN Team conducted community service activities in Krompaan Village with the aim of increasing public awareness and participation in preventing Dengue Hemorrhagic Fever (DBD). Considering that this village is located near a river, which has the potential to be a habitat for the Aedes Aegypti mosquito, effective prevention efforts are needed to prevent this disease, which is one of the infectious diseases that is still endemic in Indonesia. The spread of this disease is influenced by mobility and environmental conditions that support the breeding of the Aedes Aegypti mosquito. The community service team focused on three main objectives in this activity by providing education about the dangers of DBD, teaching how to prevent the spread of mosquitoes, and using aromatherapy candles to prevent mosquitoes. The purpose of the counseling is to reduce diseases caused by mosquitoes by teaching the community about how to live a healthy life. Used cooking oil processed into aromatherapy candles is one of the new innovations in preventing DBD. This method is considered practical and easy to implement by the community by utilizing materials available around them.